FORMULATION AND EVALUATION OF EMULGEL FROM MENTHA PIPERITA, L. ESSENTIAL OIL AS ANOPHELES MOSQUITO REPELLENT (Proceedings OPTIMAL, 2025)
Anopheles sp. mosquitoes serve as primary vectors for malaria, a disease caused by Plasmodium parasites that continues to pose a significant public health challenge globally. Mint leaves (Mentha piperita L.) possess natural repellent properties attributed to their essential oils, which produce a distinctive aroma repellent to mosquitoes. These oils contain monoterpene compounds with proven insecticidal activity, including menthol, menthone, and limonene. This study formulated and evaluated emulgel preparations from mint leaf essential oil at 20% concentration using carbopol gel bases in three variations: F1 (0.75%), F2 (1.25%), and F3 (1.75%). Conducted as a laboratory experimental study in May 2023 at the Health Polytechnic of the Ministry of Health Jayapura, the research assessed physical qualities and repellent efficacy. Organoleptic evaluations revealed no significant differences in aroma, color, or form. All formulas maintained an average pH of 6, satisfying requirements. Homogeneity and spreadability tests were compliant, while adhesion tests showed F2 failing standards (1 second). Mosquito protection averaged 26%, below the 90% benchmark. F1 emerged as the optimal formula. These findings highlight mint essential oil's potential in natural repellents, though enhancements in formulation are essential for improved efficacy.